2019
DOI: 10.20546/ijcmas.2019.804.223
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Pathogenicity and Effect of Different Culture Media on Growth and Sporulation of Alternaria brassicae (berk.) Sacc. causing Alternaria Leaf Spot Disease in Cauliflower

Abstract: caulis' meaning cabbage and 'floris', meaning flower.Cauliflower is one of the most important winter vegetables of India. India produces 8573.3 MT of cauliflower in the year 2013-14 from 433.9 ha. area with an average productivity of about 19.8mt/ha. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Results of current experiment are in line with the work of (Kumar et al, 2013) who also used Score (fungicide) and reported that it showed significant results against A. solani. Results are also supported by the study of (Valvi et al, 2019) who used seven different fungicides against Alternaria and reported that mancozeb 75% WP significantly inhibited fungal growth followed by propiconazole. Results expressed that mixture of both treatments Tilt + Moringa showed minimum disease incidence (15%) followed by Tilt (18.33%) and Moringa (32.33%) as compared to control, while in field Tilt + Moringa showed minimum disease incidence (18%) followed by Tilt (20.83%) and Moringa (34.50%).…”
Section: Assessment Of Fungicide and Plant Extract Against A Alternat...supporting
confidence: 65%
“…Results of current experiment are in line with the work of (Kumar et al, 2013) who also used Score (fungicide) and reported that it showed significant results against A. solani. Results are also supported by the study of (Valvi et al, 2019) who used seven different fungicides against Alternaria and reported that mancozeb 75% WP significantly inhibited fungal growth followed by propiconazole. Results expressed that mixture of both treatments Tilt + Moringa showed minimum disease incidence (15%) followed by Tilt (18.33%) and Moringa (32.33%) as compared to control, while in field Tilt + Moringa showed minimum disease incidence (18%) followed by Tilt (20.83%) and Moringa (34.50%).…”
Section: Assessment Of Fungicide and Plant Extract Against A Alternat...supporting
confidence: 65%
“…It has been reported that A. alternate attacks on 380 host species of plants and about 20% of agricultural spoilage is caused by Alternaria spp., with severe losses of about 80% of the crop (Bashir et al, 2014). Alternaria leaf spot is difficult to control because the fungus penetrates in infected seed, plant debris in soil and collateral hosts such as other cruciferous crops in the vicinity of the main crop or weeds (Valvi et al, 2019). One of the most effective and old method for disease control is the use of fungicides.…”
Section: Introductionmentioning
confidence: 99%